Customer satisfaction towards service quality of Keretapi Tanah Melayu (KTM) Komuter / Fathin Afryna Zulkiflee, Nur Farah Hanim Mohamad Pajri and Nur Amira Adiba Mohd Ibrahim - Zulkiflee, Fathin Afryna; Mohamad Pajri, Nur Farah Hanim; Mohd Ibrahim, Nur Amira Adiba (2019)
This research examined customer satisfaction towards KTM based on its service quality and hence investigated the service quality dimension that contributes the most towards customer satisfaction. There were five service quality dimensions that were being investigated; tangibility, reliability, responsiveness, assurance, and empathy. Descriptive Statistics, Logistic Regression, Cronbach's Alpha, and Wilcoxon Signed¬ Rank Test were performed by using IBM SPSS software to analyse the data. The findings of the study revealed that the Reliability and Assurance dimension were significantly influenced the customer satisfaction with significance value 0.014 and 0.006 respectively. Moreover, Reliability dimension was found to be the most important dimension for KTM Komuter to meet the customers' satisfaction. Based on Wilcoxon Signed-Rank Test result, this study found that there was a significant difference between expectation and perception.